PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DAN STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP BERFIKIR KRITIS DITINJAU DARI KREATIVITAS SISWA PADA MATERI SEBARAN BARANG TAMBANG DI INDONESIA (Eksperimen Pada Siswa Kelas XI SMA Negeri 3 Sragen Tahun Pelajaran 2016/2017). - Yurdayanti .; Sigit Santoso; Peduk Rintayati (Universitas Sebelas Maret (UNS), 2017)
This study aims to: (1) Distinguish differences of implementation of GI and STAD learning models to ward students critical thinking in learning geography at XI SMA Negeri 3 Sragen in academic year of 2016/2017; (2) Distinguish differences of high and low creativity toward students critical thinking in learning geography at XI SMA Negeri 3 Sragen in academic year of 2016/2017; and (3) Identify interaction of the learning models and students creativity levels toward students critical thinking in learning geography at XI SMA Negeri 3 Sragen in academic year of 2016/2017. The study conducted is a quasi-experimental research with posttest design involving two groups, an experimental group and a controlled group. Population of the study is all students of XI IPS SMA Negeri 3 Sragen 2016/2017 period with sample of the study of an experimental class and a controlled class. Data of the study is collected by using test to measure the critical thinking ability and questionnaire with Likert scale to measure the students learning creativity. Data analysis technique employed is 2 x 2 factorial analysis of variance. Results of the study conclude that: (1) GI learning model has better influence rather than STAD learning model toward the students critical thinking ability in learning geography at SMA Negeri 3 Sragen; (2) The high learning creativity students have better critical thinking ability rather than the low learning creativity students at SMA Negeri 3 Sragen;and (3) There are interaction of the learning models and students learning creativity toward the students critical thinking ability in learning geography at XI SMA Negeri 3 Sragen. The differences of critical thinking ability in learning geography are as follows: GI learning model with high creativity level has the best critical thinking ability, followed by GI learning model with low creativity level, STAD learning model with high creativity level, and the lowest is STAD learning model with low creativity level. Keywords: Learning Model, Group Investigation (GI), Student Teams Achievement Division (STAD), Learning Creativity, Critical Thinking Ability.